Weaning Age and Its Effect on the Development of the Swine Gut Microbiome and Resistome - Devin B. Holman; Katherine E. Gzyl; Kathy T. Mou; Heather K. Allen (mSystems, 2021)
ABSTRACT Piglets are often weaned between 19 and 22 days of age in North America, although in some swine operations this may occur at 14 days or less. Piglets are abruptly separated from their sow at weaning and are quickly transitioned from sow’s milk to a plant-based diet. The effect of weaning age on the long-term development of the pig gut microbiome is largely unknown. Here, pigs were weaned at either 14, 21, or 28 days of age, and fecal samples were collected 20 times from day 4 (neonatal) through marketing at day 140. The fecal microbiome was characterized using 16S rRNA gene and shotgun metagenomic sequencing. The fecal microbiome of all piglets shifted significantly 3 to 7 days postweaning, with an increase in microbial diversity. Several Prevotella spp. increased in relative abundance immediately after weaning, as did butyrate-producing species such as Butyricicoccus porcorum, Faecalibacterium prausnitzii, and Megasphaera elsdenii. Within 7 days of weaning, the gut microbiome of pigs weaned at 21 and 28 days of age resembled that of pigs weaned at 14 days. Resistance genes to most antimicrobial classes decreased in relative abundance postweaning, with the exception of those conferring resistance to tetracyclines and macrolides-lincosamides-streptogramin B. The relative abundance of microbial carbohydrate-active enzymes (CAZymes) changed significantly in the postweaning period, with an enrichment of CAZymes involved in degradation of plant-derived polysaccharides. These results demonstrate that the pig gut microbiome tends change in a predictable manner postweaning and that weaning age has only a temporary effect on this microbiome. IMPORTANCE Piglets are abruptly separated from their sow at weaning and are quickly transitioned from sow’s milk to a plant-based diet. This is the most important period in commercial swine production, yet the effect of weaning age on the long-term development of the pig gut microbiome is largely unknown. Metagenomic sequencing allows for a higher-resolution assessment of the pig gut microbiome and enables characterization of the resistome. Here, we used metagenomic sequencing to identify bacterial species that were enriched postweaning and therefore may provide targets for future manipulation studies. In addition, functional profiling of the microbiome indicated that many carbohydrate and metabolic enzymes decrease in relative abundance after weaning. This study also highlights the challenges faced in reducing antimicrobial resistance in pigs, as genes conferring tetracycline and macrolide resistance remained relatively stable from 7 days of age through to market weight at 140 days despite no exposure to antimicrobials.